What is Post(-)colonialism? Problems with the Definitions - CHEHBOUB, Fakia (Journal of Human Sciences, 2015)
There is much continuing debate and disagreement among critics as to the meaning of the term Post(-)colonialism, and indeed even its spelling whether with or without the hyphen. Indeed, agreeing on one simple definition of Postcolonialism is difficult due to many reasons and the dispute over its exact meaning and precise definition seems to be unresolved. The present article is an attempt to define Post(-)colonialism, and thus to point to its major preoccupations and areas of concern. It also aims to draw some debate about the use of the terms “Post-colonial” and “Postcolonial” in some recent publications.